Air Pollution as Gendered Oppression: An Intersectional Feminist Analysis - Windy Dwi Ariyanto; Mia Siscawati; Hariati Sinaga (Politeknik Siber Cerdika Internasional, 2026)
Background: Air pollution is commonly treated as a technical environmental issue, although its impacts are socially unequal and shaped by gender, class, geography, and access to resources. Women experience disproportionate burdens due to reproductive vulnerability, household exposure, unpaid care responsibilities, and limited participation in environmental decision-making. Objective: This article examines air pollution as a gendered problem by positioning women not as statistical objects of exposure but as subjects whose lived experience constitutes a source of knowledge. Methods: Drawing on scholarly literature, air pollution was analyzed as a layered form of oppression that situates women at the intersection of biological vulnerability, the domestic division of labor, class position, geographical location, and constrained economic access and health services. Results: Three theoretical frameworks are integrated: Crenshaw's concept of intersectionality with its structural, political, and representational dimensions; Rocheleau's feminist political ecology, foregrounding access, control, knowledge, and struggle over environmental resources; and Elmhirst's extension, which insists that the relations among gender, environment, and power be read through the social, economic, and political structures that govern resource access and distribute ecological vulnerability. Conclusion: The analysis shows that women are simultaneously the most exposed, the most burdened by care work, the least in control, the least represented, and the most frequently uncounted. Gender-blind clean-air policy therefore tends to deepen rather than ease inequality.